The Influence of Effective Emergency Medical Teams and Antecedents on the Smart Emergency Service System in Northern Thailand - Patchetphokin, Kritwaroj; Chatluang, Sophannar; Kiatigosnusorn, Jiraporn (The Bangkok Medical Journal, 2025)
OBJECTIVES: This research studies a causal relationship model of knowledge management (KM; systematic creation, sharing, and utilization of organizational knowledge), safety climate (SCL; collective perceptions of safety policies and practices), information technology capabilities (ITC; digital infrastructure and competencies), and effective emergency medical teams (EFT; coordinated performance of multidisciplinary responders) to smart emergency medical services (SEMS; technology-enhanced, data-driven emergency care systems) in Northern Thailand. MATERIALS AND METHODS: This study employed a mixed-methods design with an explanatory sequential approach. In the quantitative phase, data were collected from 550 emergency medical services (EMS) personnel working in the public EMS system across Northern Thailand, selected through proportionate stratified random sampling to ensure representation by service type and geographic area. Eligible participants had at least one year of EMS experience, were literate in Thai, and provided informed consent; those unable to communicate in Thai or unwilling to participate were excluded. In the qualitative phase, three EMS experts with leadership roles and ≥ 5 years of professional experience were purposively recruited for in-depth interviews to contextualize and enrich the survey findings. Data analysis included descriptive and inferential statistics. Measurement model reliability and validity were assessed using confirmatory factor analysis (CFA), composite reliability (CR), and average variance extracted (AVE). Path coefficients were estimated using structural equation modeling (SEM) with maximum likelihood estimation (MLE), and statistical significance was determined through t-statistics generated by LISREL. RESULTS: KM showed strong positive effects on ITC (β = 0.818, p < 0.001) and SCL (β = 0.883, p < 0.001), but no statistically significant direct effect on EFT (β = 0.056, not significant). SCL positively influenced EFT (β = 0.401, p < 0.05), ITC positively influenced SEMS (β = 0.125, p < 0.05), and EFT had the strongest effect on SEMS (β = 0.882, p < 0.001). KM exerted a significant indirect effect on SEMS through SCL and EFT (β_indirect = 0.312). CONCLUSION: The study underscores the critical role of KM in enhancing EMS, SCL and EFT, demonstrating a transformative approach to improving healthcare response in Northern Thailand’s challenging geographical context.